Determinants of Income Diversification Strategies among Agricultural Households in the Philippines using National Survey Data - Ferdinand D. Anabo (Philippine Social Science Journal, 2021)
Household income diversification is a critical pathway to improve the living standard of agricultural households. It is the process by which households actively seek to increase the number of income-generating activities. This study sought to describe the prevalence and patterns of income diversification among agricultural households and to identify the factors related to the degree of income diversification. The study applied a quantitative research design using a cross-sectional survey from the Philippine Statistics Authority. The fractional response regression model was used to determine the factors affecting income diversification. Results revealed that most of the household samples have two income sources. Most come from agricultural labor, crop farming, and gardening. Factors related to income diversification are sex, age, education, family size, being married, agricultural income, access to credit, cash support, access to electricity and water, access to information and communication, and vehicle ownership.